Efektivitas Kompres Aloe Vera dan Kompres Hangat terhadap Pembengkakan Payudara pada Ibu Post Partum di klinik Rizky Anugrah Tanggerang Tahun 2023 - Magdalena Tri Putri Apriyani; Ageng Septa Rini (Elisabeth Health Jurnal, 2023)
Background: Swollen breasts are damming of milk due to narrowing of the lactiferous ducts or by glands that are not completely emptied. Swelling of the breasts is a problem that often arises in postpartum mothers. It usually occurs on the third to fourth day after delivery. Purpose : "Effectiveness of Aloe Vera Compresses and Warm Compresses for Swelling of the Breasts at the Rizky Anugerah Tangerang Clinic in 2023". Method: quasy experiment with non-equivalent control group design with Wilcoxon analysis Signed Rank Test. The population in this study was 50 and the sample in this study was 30 respondents, using the random sampling technique. The research instrument used was an observation sheet. Results: The results of the analysis showed that there was an effect of giving aloevera compresses on the reduction of breast swelling in post partum mothers. Based on the statistical test results, the ρ value is 0.05 <0.05, so H0 is rejected and H1 is accepted. Keywords: Aloe Vera, Breast Swelling, Warm Compres